Factors Affecting Premarital Sexual Behavior in Adolescents in South Sumatra - Purnama Sari, Indah; Nasution, Sri Lilestina; Lailatul Alfiah (Jurnal Ilmu Kesehatan Masyarakat, 2022)
Adolescence is one of the stages of the individual growth and development cycle in the age range of 10-24 years and is not yet bound by marital status. One of the risky sexual behaviors that most teenagers do is dating. Dating in adolescence is part of the socialization process, learning intimacy and providing opportunities to create meaningful and unique relationships with the opposite sex, as well as being a context for sexual experimentation and exploration. This study’s aim was to determine various factors associated with premarital sexual behavior at risk in adolescents. This study uses secondary data with a cross sectional design from the 2018 Survei Kinerja dan Akuntabilitas Program Kependudukan, Keluarga Berencana dan Pembangunan Keluarga (SKAP) with a total of 637 adolescents aged 15-24 years and unmarried were selected as a weighted samples. Data was collected through interviews using structured questionnaires, and data analysis was carried out using univariate, bivariate using Chi Square’s test, and multivariate using logistic regression tests. The proportion of risky premarital sexual behavior in adolescents in South Sumatra was 62,4%. Adolescents with higher knowledge about reproductive health had 2.7 times of risk of premarital sexual behavior than else after being controlled by knowledge of family planning, socioeconomic and residence (95% CI: 1.8 – 3.9). This study concludes that knowledge is one of the factors that influence premarital sexual behavior but is not a direct factor. Therefore, the advice that can be given is to involve various parties comprehensively in providing knowledge in a sustainable manner.